DOES THE INQUIRY LEARNING MODEL HAVE AN IMPACT ON SOCIAL ATTITUDES AND RESPONSIBLE CHARACTER? - Astalini, Astalini; Darmaji, Darmaji; Kurniawan, Dwi Agus; Perdana, Rahmat; Andriyanto, Andriyanto (LPPM Universitas Jambi, 2024)
This groundbreaking research endeavors to unveil the transformative potential of the inquiry learning model, transcending its conventional academic applications to delve into its profound impact on high school students' social attitudes and responsible character. Employing an innovative mixed methods research design, this study pioneers a comprehensive analysis that seamlessly integrates quantitative and qualitative methodologies. Through the meticulous administration of a carefully constructed questionnaire, the research uncovers compelling insights gleaned from sophisticated t-test and regression analyses. Results illuminate a significant correlation between students' social attitudes and responsible character, highlighting the intricate interplay between these pivotal dimensions of adolescent development. Furthermore, regression analysis reveals the substantive influence of the inquiry learning model in fostering positive social attitudes and instilling a sense of responsibility among students. Novelty is intrinsic to this research, as it boldly ventures beyond traditional academic metrics to prioritize the cultivation of empathy, integrity, and civic engagement among learners. By challenging established educational paradigms, this study advocates for a transformative shift that recognizes inquiry-based approaches as catalysts for nurturing well-rounded individuals poised to effect positive societal change. Ultimately, this research represents a paradigmatic advancement in education, emphasizing the indispensable role of pedagogy in shaping not only intellectual acumen but also moral fortitude and social consciousness.